Mathematics E-Comic Media Based on Local Wisdom of Jejaitan in Identifying Angles Material for Fourth Grade Elementary Students - Ni Ketut Puri Arniti; Anak Agung Gede Agung (Universitas Pendidikan Ganesha, 2025)
Students' low learning outcomes in understanding angle concepts in Mathematics are caused by the lack of innovative and contextual learning media. Learning is still dominated by lecture methods, making it difficult for students to grasp the material. This study aims to design, assess feasibility, and evaluate the effectiveness of e-comic media based on the local wisdom of jejaitan in enhancing students' understanding. This research employs Research and Development (R&D) using the ADDIE model. The study involved 24 fourth-grade students from elementary school and several experts as validators. Data were collected through questionnaires and tests, then analyzed using validity, reliability, and effectiveness tests with a one-sample t-test. Results showed that the e-comic received a very high validation score, exceeding 90%. The effectiveness test demonstrated a significant improvement, with tvalue = 2.314 greater than ttable = 1.714 (p < 0.05). This study concludes that e-comic media based on local wisdom of jejaitan is effective for Mathematics learning. The implication is that digital and culture-based media can enhance learning quality and encourage educators to develop more engaging and contextual strategies.